2017
DOI: 10.4238/gmr16039680
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Molecular mapping and candidate gene analysis for resistance to powdery mildew in Cucumis sativus stem.

Abstract: ABSTRACT. Powdery mildew (PM) of cucumber (Cucumis sativus), caused by Podosphaera xanthii, is a major foliar disease worldwide and resistance is one of the main objectives in cucumber breeding programs. The resistance to PM in cucumber stem is important to the resistance for the whole plant. In this study, genetic analysis and gene mapping were implemented with cucumber inbred lines NCG-122 (with resistance to PM in the stem) and NCG-121 (with susceptibility in the stem). Genetic analysis showed that resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The inheritance of PM resistance is complicated in cucumber. Few studies reported that PM resistance was controlled by a recessive gene [ 9 , 10 ]. Most studies showed that PM resistance was a quantitative trait that controlled by multiple genes and likely recessively inherited in cucumber [ 11 , 12 , 16 , 17 , 18 , 19 , 21 , 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inheritance of PM resistance is complicated in cucumber. Few studies reported that PM resistance was controlled by a recessive gene [ 9 , 10 ]. Most studies showed that PM resistance was a quantitative trait that controlled by multiple genes and likely recessively inherited in cucumber [ 11 , 12 , 16 , 17 , 18 , 19 , 21 , 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cucumber, QTLs for PM resistance have previously been detected on chromosome 5 in an interval where the CsaMLO8 gene is located [ 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 24 , 25 ]. In the CG population, the QTL pmG5.4 is colocalized with CsaMLO8 , and the CG lines carrying the mutant allele (with TE insertion) of CsaMLO8 [ 28 ] showed a significant reduction of disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single recessive gene pm for PM resistance in leaves has been mapped to an approximately 468 kb region on chromosome 5 in IL52 ( Zhang et al, 2018 ). The resistance to PM in the stem of NCG-12 is also controlled by a single recessive nuclear gene ( pm-s ) ( Liu et al, 2017 ). The recessive inheritance of PM is not convenient to use in cucumber breeding ( Xu X. et al, 2016 ).…”
Section: Inheritance Quantitative Trait Loci Mapping and Candidate Ge...mentioning
confidence: 99%
“…Among the QTLs, the QTL pm 1.1 and the pm 5.2 are effective in leaf and hypocotyl resistance [20]. Some candidate genes of powdery mildew resistance were suggested, which included the MLO-like gene [21,23], Csa1M064780, Csa1M064790 [24], the CsSGR gene [25], the cyclin-like (cyclin L) gene, genes encoding the F-box protein, kinesin protein, calcium transporting ATPase, Ras-related protein, and lysine-specific histone demethylase 1 (LSD1) [15]. Interestingly, the powdery mildew resistance is reported to be closely linked to the downy mildew resistance [16,22].…”
Section: Introductionmentioning
confidence: 99%